Anxiety Level of Inpatient Families in General ICU Room of St. Anthony Hospital Pontianak - Seriaka; Roselina; Sari Sarce (PT FORMOSA CENDEKIA GLOBAL, 2023)
The condition of patients who are treated in intensive care causes families to become depressed and feel anxious. This study aims to describe the level of anxiety of families of inpatients in the General ICU room of St. Antonius Hospital Pontianak, This research method is quantitative using a descriptive design, The population in this study is the family of patients treated in the General ICU room of St. Antonius Hospital Pontianak with a sample of 42 people and the sampling technique in this study uses accidental sampling. The results showed that almost half of the respondents, namely 17 people (41%) had mild anxiety, as many as 11 people (26%) were seriously anxious, a small percentage of 7 people (17%) were not anxious, a small part of 6 people (14%) were moderately anxious, and a small part of 1 person (2%) was panicked. Families of patients admitted to the ICU mostly have mild anxiety. Future suggestions for nurses to approach psychologically, as well as improve skills in conducting behavioral therapy to reduce anxiety.